Comparison of some physiological markers prior to and post vitrification in Hypericum perforatum L. - Urbanova, M; Skyba, Matus; Toteva, V. Kapchina; Danova, K; Cellarova, E (MTT, 2008)
The aim of this work is to present the differences between survival rate of Hypericum perforatum L. shoot tips cryoprotected with PVS2 or PVS3 and to compare some physiological patterns prior to and post vitrification procedure. H. perforatum shoot tips pretreated either with 0.076ìM abscisic acid (ABA) for 10 days or 0.3M sucrose for 16 hours were cryoprotected with two different cryoprotective solutions, PVS2 (10% v/v glycerol, 20% w/v sucrose, 10% v/v DMSO) or PVS3 (50% w/v sucrose, 50% v/v glycerol). Survival rate was determined 7 weeks after thawing. As Table 1 shows we have observed 1.47 to 8.6 times higher survival rates (except for the genotypes 40/7/3 and 42/7/3) using PVS3 after ABA pretreatment, whereas in case of sucrose pretreatment survival rate of most genotypes exposed to the same cryoprotection procedure decreased (except for 29/7/5 and 34/7/1, respectively). Recovered plants were subjected to assessment of some physiological markers. Conductivity, H2O2 and MDA content were determined in recovered samples and their control plants (up to 100 mg FW). Our preliminary results indicate that at least one of the parameters studied exceeded level of control values (prior to cryopreservation) after recovery of cryopreserved samples (Figure 2) with an exception of one sample. Possible effect of these findings will be presented and discussed.
Keywords: Ka; abscisic acid (ABA); cryoprotective solutions; sucrose pretreatment